Cystic hygroma and increased nuchal translucence, markers of chromosomal anomalies - G, Moisés Huamán (2013)
Objectives: To determine the importance of nuchal translucence in fetuses 11 to 13 +6 weeks, identifying characteristics, association with chromosomal anomalies and differences between cystic hygroma and increased nuchal translucency. Design: Prospective cross-sectional study. Setting: Instituto Latinoamericano de Salud Reproductiva, Lima, Peru. Participants: Pregnant women and their fetuses with prenatal cytogenetic diagnosis. Interventions: Between 2007 and June 2012, 266 cases with prenatal cytogenetic diagnosis had 230 amniocentesis after 14 gestational weeks and 36 chorionic villi biopsy (CVS) between 11-13 gestational weeks. Main outcome measures:Prenatal ultrasound markers. Results: One hundred and six cases of chromosomal abnormalities (39.9%) were found. Cystic hygroma (CH) was more often found than nuchal translucency (NT) (30.8% versus 11.3%) associated with chromosomal abnormalities (68.3% versus 31%), corresponding to HQ sensitivity (S) 45%, positive predictive value (PPV) 62%, likehood ratio+ (LR+) 2.4, and for increased TN S 11%, PPV 40%, LR+ 1. CH was associated in 35.7% to monosomy X, and NT to trisomy. Conclusions: CH was the most common chromosomal abnormalities’ marker found between 11 and 13 +6 weeks and had greater predictive value than increased NT. Each would represent separate entities requiring differentiation.Key words: Cystic hygroma, nuchal translucency, chromosome abnormality.